Isolasi Bakteri Asam Laktat dari Makanan Tradisional Pakasam Ikan Kapiek (Barbonymus schwanenfeldii) yang Berpotensi Sebagai Kandidat Agen Probiotik, Antibakteri dan Biopreservatif - Cici Sri Wahyuni; Tetty Marta Linda; Bernadeta Leni Fibriarti (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to isolate Lactic Acid Bacteria (LAB) from traditional fermented food of kapiek fish (Barbonymus schwanenfeldii) from Pangkalan Serai Village, Kampar Kiri Hulu, Riau which has antibacterial activity and is a candidate for biopreservative agent. The methods used in this study were isolation, partial characterization, antibacterial activity test, and biopreservative test. The results showed that the initial isolation and characterization of pakasam obtained 2 isolates (isolate P1 and isolate P2) known as the genus Enterococcus spp. and 3 isolates (isolate P3, isolate P4 and isolate P5) from the genus Lactobacillus spp. Isolate P5 has the potential as a candidate for probiotic agent because it can grow at pH 3, extreme salt content, and has broad-spectrum antibacterial activity. Isolate P5 has the potential as a candidate activity against Escherichia coli ATCC 35128 of 8.5 ± 0.8 mm and Staphylococcus aureus ATCC 29213 of 6.6 ± 0.1 mm after the cell-free supernatant was heated for 15 minutes at 100ºC. Key words: Lactic Acid Bacteria, Pakasam, Probiotics, Biopreservative